2014 16th European Conference on Power Electronics and Applications 2014
DOI: 10.1109/epe.2014.6910961
|View full text |Cite
|
Sign up to set email alerts
|

Power electronic losses of a customer-end inverter in low-voltage direct current distribution

Abstract: A low-voltage direct current (LVDC) distribution system comprises a rectifier, a DC network, and customer-end inverters (CEI) responsible for the AC supply to the electricity end-users. The CEIs can be implemented as single-phase or three-phase ones; in this paper, feasible single-and three-phase topologies are introduced and their losses are calculated using nine different power switches. Three commercially available IGBT, MOSFET, and SiC MOSFET power switches are selected for comparison. In this application,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…LVDC provides better infrastructure for managing local generation/loads to enable stable and optimal islanded operation. For example, the LVDC with a central BESS trial site reported in [13] can provide power for the relevant customers for 5 hours in the case of the main grid outages. The project detailed in [14] has also replaced an existing islanded AC microgrid by an LVDC microgrid to improve the management of the network.…”
Section: Lvdc Distribution Network For Rural Areasmentioning
confidence: 99%
“…LVDC provides better infrastructure for managing local generation/loads to enable stable and optimal islanded operation. For example, the LVDC with a central BESS trial site reported in [13] can provide power for the relevant customers for 5 hours in the case of the main grid outages. The project detailed in [14] has also replaced an existing islanded AC microgrid by an LVDC microgrid to improve the management of the network.…”
Section: Lvdc Distribution Network For Rural Areasmentioning
confidence: 99%
“…II, it should be observed that when a controllable switch turns on the opposite free-wheeling diode turns off and in both of them there are losses (switch-on and reverse recovery, respectively). The vectors of the turn-on and turnoff switching losses (sw-on & sw-off) of the IGBT and the reverse recovery losses (rr) of the diode are given by [9] p abc sw-y,igbt (t) = f sw E sw-y I c-ds…”
Section: B Switching Lossesmentioning
confidence: 99%
“…(9) (9) describes the turn-on and turn-off switching losses and reverse-recovery losses of a 2L-VSI depending on preceding (9). It can be seen that all the other terms on the right-hand side of (9) equal zero and vanish; either because of (1 3 −d[k]) = 0 (second and fourth term) or (I 3 −S abc [k−1]) = 0 (third term).…”
Section: B Switching Lossesmentioning
confidence: 99%
See 2 more Smart Citations